Impact of Operations and Information Management in a Banking Service Provider - Abu Ghneim, Azhar Nema (International Journal of Supply Chain Management, 2019)
Nowadays competition condition to improve service quality is a key strategic issue for organizations operating in the service sector. The study aims to determine the nature of the relationship of the operations and information management in group of Iraqi banks as a field of study, has reached the community of the study (422) of them were approved (151) employees sample of the study was conducted statistical analysis on questionnaire forms (151) by a number of advanced statistical programs and analyzed by smart v3 and SPSS v20. The problem of the study showed a knowledge gap about the interpretation of the nature of the relationship between the variables of the current study of the independent variable and the sense of belonging and the dependent variable balancing behaviors in the workplace. The study found a number of practical results, including that there is a relationship of direct moral impact to the sense of belonging and balance of behaviors in the workplace The results of the study can be used as attention to the psychological affiliation of workers leads to the achievement of balanced behaviors in the workplace and the interest in the psychological affiliation and promotion Will increase the opportunities for banks to achieve their objectives.